PENGARUH GEOMETRI PAHAT, TEBAL PEMAKANAN DAN JENIS PAHAT TERHADAP KEAUSAN DAN KUALITAS KEKASARAN PERMUKAAN HASIL PROSES PEMBUBUTAN BENDA KERJA BAJA AISI 1045 MENGGUNAKAN MESIN CNC QTN 100 U - Joko Waluyo (SIMETRIS, 2020)
In the manufacturing industry the use turning machine has increased significantly, considering that the resulting production has a much better level of quality than conventional lathes. In the CNC machining process parameters greatly affect the quality of surface roughnees and the wear tools used in the machining proccees. The aim of this research is to obtain optimum surface quality and minimal tool smoothness with CNMG and DNMG tool materials. The parameter of the tool angle used are 800 and 550 with athickness of 1 mm, 0,5 mm and a cutting speed of 300 m/minute and feeding 0,25 mm/rotation. The result of the research that the optimum surface roughness values for CNMG and DNMG tool materials were 2,33 µm and 5,01 µm for cutting with a thickness of 1 mm and for cutting with a thicknes of 0,5 mm the roughness value were 1,44 µm and 2,33 µm. Tool wear with CNMG material with tool angle geometry 800 the amount of wear for cutting with a thickness of 1 mm and 0,5mmis 0,016 mm and 0,024mm, for tool 550 with DNMG material, the cutting thicknees of 1mm and 0,5 mm is 0,023 and 0,035 mm.